On the Timing of Marriage, Cattle and Weather Shocks - Hans Hoogeveen; Bas van der Klaauw; Gijsbert van Lomwel (Tinbergen Institute, 2004)
In this paper we focus on the timing of marriages of women, whose marriages are associated with bride wealth payments, which are transfers from (the family of) the groom to the bride's family. Unmarried daughters could therefore be considered assets who, at times of need, can be cashed in. We investigate both theoretically and empirically to what extent the timing of a marriage of a daughter is affected by the economic conditions of the household from which she originates. We distinguish household specific wealth levels and two types of shocks: correlated (weather) shocks and idiosyncratic (wealth) shocks. We estimate a duration model using a unique panel survey of Zimbabwean smallholder farmers. The estimation results support the hypothesis that the timing of marriage is affected by household characteristics; girls from households that experienced a negative idiosyncratic (wealth) shock are more likely to marry.
Keywords: Q12; C4; J12; D13; D91; 330; coping strategies; bride wealth; duration models; wealth shocks; dynamic programming model; Familienökonomik; Ländlicher Raum; Intergenerationale Übertragung; Nutztiere; Simbabwe; Wetter